Digital competence of preservice teachers of pre-school and primary education: a multiple comparisons study - Enrique Alastor; Francisco David Guillén-Gámez; Julio Ruiz-Palmero (Grupo de Investigación "Nodo Educativo" / Red Universitaria de Tecnología Educativa (RUTE), 2024)
Digital competence is an essential element for the initial training of teachers, as it allows them to integrate digital technologies into their teaching practice. Therefore, the purposes of this study were: (1) to know the self-perceived level of future teachers of Primary Education and Early Childhood Education regarding their digital competences; (2) to compare if there are significant differences in the digital competences between the future teachers of both educational stages; and (3) to identify if there are significant differences in the competences of the future teachers between the different academic courses of the educational degree, for each educational degree. To achieve the objectives, a non-experimental ex post facto study was carried out with a sample of 897 students from the Infant and Primary degrees. The results showed that future teachers have a medium-high self-perceived level of digital competence in both educational degrees, finding significant differences between future teachers of Early Childhood Education and Primary Education, being the latter those who obtained higher scores. For future teachers of the Early Childhood Education stage, significant differences were found between the students of the first and fourth year, while for those of Primary Education, differences were found between all the academic courses, except between the third and fourth. These results suggest that initial teacher training should focus on the development of the digital competences of future teachers, with special attention to the first academic courses.